Surface discrepant manifestation, regime and controlling mechanisms of hydro-thermal behaviors in a typical high-temperature geothermal system on Tibetan Plateau - Yong Xiao; Yuqing Zhang; Jie Wang; Gongxi Liu; Peng Zhou; Huizhu Chen; Wenxu Hu; Liwei Wang; Limao Qin; Lianhe Zhou; Pengtian Ma; Qiong Pu (Journal of Hydrology: Regional Studies)
Study region: Quzhuomu Geothermal Valley, a typical high-temperature geothermal valley on Tibetan Plateau. Study focus: This research focuses on the surface differential manifestations of hydro-thermal activities in high-temperature geothermal fields and their controlling mechanisms. New hydrological insights for the region: Hydro-thermal manifestations within the valley exhibit significant spatial variations in water temperature, hydrochemical and isotopic compositions, as well as the travertine deposition. Geothermal water presents a sequential increase in outcropping average temperatures, from 53.5℃ upstream to 60.5℃ midstream, and finally to 80.8℃ downstream. Geothermal waters hydrochemical facies evolve from SO₄·HCO₃·Cl-Na·Ca type to Cl·HCO₃-Na type along the valley, accompanied by increasing travertine deposition area. The geothermal system receives water recharge from the Kongbu Mountain, which is heated by the magma chamber (reserve temperature 130–180℃). The heated waters upwell through different faults, resulting in varying circulation depths, residence times, and extents of water-rock interaction for the geothermal waters, and encounter different degrees of cold-water mixing (from 71 % upstream to 55 % downstream). These factors collectively lead to distinct hydro-thermal manifestations of the geothermal system at the ground surface. An integrated conceptual model was established to reveal the distinct hydro-thermal manifestations at ground surface within a geothermal field and behind reasons. This research could enhance understanding of hydro-geothermal behavior regimes of high-temperature geothermal systems, and be beneficial for global geothermal energy exploration and geothermal hazard mitigation.